The Influence Domestic Investment and Foreign Investment on Economic Growth in Central Java (Period 1985-2020) - Firsca Febrina Lusardi; Karnowahadi - Karnowahadi; Rustono - Rustono (Admisi dan Bisnis, 2022)
Investment is an important factor to development and support economics growth in a region. This study aims to determine the effect of Domestic Investment (PMDN) and Foreign Investment (PMA) on Economic Growth in Central Java. This study uses secondary data obtained from the Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Provinsi Jawa Tengah and Badan Pusat Statistik Provinsi Jawa Tengah using the documentation and literature study method, the time period used from 1985 to 2020. The total sample used was thirty-six. The analytical method used is multiple linear regression. The results of the analysis used were based on the Adjusted R2 test, Anova test (F test) and Partial test (t-test). From the results of the R2 value, the independent variables have an effect of 70.8% on the independent variable while the remaining 29.2% is influenced by other variables. Based on the partial test, the Domestic Investment (PMDN) variable has a significant effect on Gross Regional Domestic Product (GRDP) while the Foreign Investment (PMA) variable has no significant effect on Gross Regional Domestic Product (GRDP). Based on the presentation of the test results, the Regional Government can increase investment to support development so as to increase economic growth in the Central Java Province.